Walk 13 MEETINGS WITH GAIDAI - Lidin, Konstantin; Grigoryeva, Elena; Chumakov, Sergey; Makogon, Lyubov (project baikal, 2014)
Walk 13 MEETINGS WITH GAIDAI Leonid Gaidai’s House Development of Gaidai Boulevard Extension of East-Siberian Railway School-Lyceum №42 on Profsoyuznaya Street Administration and Amenity Building Ponton Bridge Habitable Bridge in Irkutsk. Term Theses